A technique to optimize isocenter co-ordinate and collimator angle in radiosurgery planning for multiple brain metastases - Pham Hong Lam; Phan Tien Manh; Pham Quang Trung (Nuclear Technology and Radiation Protection, 2025)
Collimator angle optimization software CAOS was developed in Python and integrated with the Eclipse 13.6 platform to support stereotactic radiosurgery treatment planning. Twenty-five cases of multiple brain metastasis (10 with two lesions, 10 with three, and 5 with four) were planned using stereotactic radiosurgery in Eclipse 13.6, followed by optimization with CAOS. Eclipse uses a conventional method, while CAOS software first determines the isocenter co-ordinate and then optimizes the collimator angles. The CAOS-optimized plans exhibited significantly improved dosimetric outcomes in stereotactic radiosurgery planning. They reduced gradient index and gradient measure values for the tumor, decreased the mean normal brain volume receiving 12 Gy, and lowered the maximum dose to organs-at-risk, compared to Eclipse plans.